Sistem Monitoring Suhu, Kelembaban, dan Pengendali Penyiraman Tanaman Hidroponik menggunakan Blynk Android - Wahyu Adi Prayitno; Adharul Muttaqin; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Hydroponics is a method of farming that does not use soil as a growing medium, but only use water containing nutrients that plants need. One of the factors success of planting with this method is affected by how the owners do care for the plants. Primary the treatments are done to ensure the circulation of nutrients or watering is given a timely manner in sufficient quantities. There was a time hydroponic plant owners are not anywhere near the planting area so that is not directly taking care of the plants. In order for hydroponic plant owners will still be able to care for and monitor the environmental conditions of the plant although it is far from the planting site, the project in this paper provides an alternative solution to overcome these problems. Device made in this project combining the capabilities of arduino mega as a data acquisition system incorporating ethernet shield for data transmission through the Internet, DHT11 sensor to read the temperature and humidity, special applications android blynk as monitoring tools, and RTC for timing in realtime. Arduino Mega is also associated with ignition relay to set the sprinkler pumps or circulatory water. Based on testing conducted found that each module can work well according to its function. With the appropriate network quality testing (average delay to blynk server is 1242ms, obtained by the process of sending commands and execution watering and environmental data delivery takes about 1-2 minutes.